FAKTOR PENYEBAB PUTUS SEKOLAH PADA PENDIDIKAN DASAR DIDESA NUMBING KECAMATAN BINTAN PESISIR KABUPATEN BINTAN - Veriyana, Deriska Brenda Veriyana Brenda; ', Sumarno; ', Ngadla (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to (1) To determine what educational factors cause children to drop out of school at the basic education sub-district village numbing Coastal Bintan Bintan regency. (2) To determine what educational non cause dropouts in primary education in villages numbing Coastal District of Bintan Bintan regency. (3) To determine the most widely experienced dropouts in primary education in villages numbing Coastal District of Bintan Bintan regency.The population in this study are all dropouts in 2011-2013. The sampling based on proportional sampling. Data were collected through a questionnaire. While data analysis using univariate analysis, validity test and reliability test significant level of 0.05%.Based on the results of the study factors causing dropouts in primary education the most widely experienced didesa numbing Coastal District of Bintan Bintan regency namely education factor consisting of the indicators the inability of students to capture and receive lessons in school, inadequacy of teachers in teaching and educating, unfavorable assessment system, and school or class that has a less favorable outcome highest percentage of respondents who answered statement agreed to by 71.80%.Advice can be given that because of the dropouts in primary education, then the public should be able to change his views with the view advanced to education. Keywords: factors, dropout, basic education.